Profile of adult patients with COVID-19 admitted to an intensive care unit (Research, Society and Development, 2022)
Objectives: To know the profile of adult patients who required hospitalization in intensive care units at Hospital Naval Marcilio Dias, a military institution, located in the city of Rio de Janeiro. Methodology: Quantitative study, with a descriptive and cross-sectional approach, mediated by documentary analysis. The universe of the study were the medical records of patients aged 18 to 59 years with confirmed diagnosis for coronavirus and who required hospitalization in intensive care unit in the period from March 2020 to September 2021. Results: By accessing the medical records a final (n) of 176 patients within the age range comprised in the study was identified, with a focus on characterization of the participants; therapies implemented and complications/iatrogenies presented by patients in the intensive care units. Final considerations: A change in the age profile of patients with COVID-19 in the severe and critical forms was noticed, identifying the profile of higher prevalence in characteristics such as male gender, age between 50 and 59 years, comorbidities such as hypertension, obesity and diabetes mellitus among others.